2014
DOI: 10.1021/pr500652y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Proteins Involved in Human Sperm Motility Using High-Throughput Differential Proteomics

Abstract: Mammalian sperm motility is a prerequisite for in vivo fertilization, and alterations in this parameter are commonly observed in infertile males. However, we still do not have a complete understanding of the molecular mechanisms controlling it. The aim of this study was to identify proteins involved in human sperm motility deficiency by using TMT protein labeling and LC-MS/MS. Two complementary approaches were used: comparison between sperm samples differing in motility (asthenozoospermic versus normozoospermi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
115
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 152 publications
(138 citation statements)
references
References 75 publications
12
115
0
2
Order By: Relevance
“…Although clearly still in its infancy, the application of metabolomics to the study of human spermatozoa has a huge potential, and its application as a phenotypic readout can be an important key to understand fundamental biological processes acting in human sperm cells and also to better comprehend distinct male reproductive pathologies, and perhaps to discover new (in)fertility biomarkers. Particularly interesting should be the future application of these techniques to study different types of sperm phenotypes and to determine whether significant differences in the abundance of specific metabolites can be identified, such as those that have been recently detected at the protein level Amaral et al, 2014b;Azpiazu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Although clearly still in its infancy, the application of metabolomics to the study of human spermatozoa has a huge potential, and its application as a phenotypic readout can be an important key to understand fundamental biological processes acting in human sperm cells and also to better comprehend distinct male reproductive pathologies, and perhaps to discover new (in)fertility biomarkers. Particularly interesting should be the future application of these techniques to study different types of sperm phenotypes and to determine whether significant differences in the abundance of specific metabolites can be identified, such as those that have been recently detected at the protein level Amaral et al, 2014b;Azpiazu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Cluster 2, 3 and 5 on the other hand, had majority of the pathways common with AZS samples and cluster 4 had overlapping pathways with NZS samples. 4. DISCUSSION Twenty-four percent of infertile men present with isolated AZS (14) caused by various factors including varicocele, infection or genetic causes (15)(16)(17).…”
Section: Validation Of Pathways By Clustering Proteins By Self Organimentioning
confidence: 99%
“…With the NextGeneration Sequencing (NGS) technology, RNA-Seq has become a powerful tool for transcriptomic profiling (19,20). Tandem mass tags (TMT)-based quantitative proteomics has been widely used and proven to be a reliable method for determining protein expression levels (21)(22)(23). Here, we demonstrated that an integrated study coupling NGS-based RNASeq transcriptomics and quantitative TMT-LC-MS/MS proteomics has gained a system level understanding of the functional components involved in acclimation to HL.…”
mentioning
confidence: 99%